Removal of Name of Ophthalmologist from IMR for Six Months for Violation of Ethical Regulations, 2002: NCDRC (Indian Internet Journal of Forensic Medicine and Toxicology, 2022)
This case pertains to alleged medical negligence against the Opposite Party wherein it was alleged that the Complainant lost his left eye after the Cataract surgery. The District Forum held it was a medical negligence case and awarded compensation of Rs. 200000/- along with 12% interest from the date of filing of the Complaint. The Order of the District Forum was appealed by the OP before the State Commission. The Appeal was allowed and consequently the Complaint was dismissed. Being aggrieved the Complainant filed the Revision Petition before NCDRC, which perused the material on record, the prescriptions of different hospitals including AIIMS, New Delhi and inter-alia the MCI Order dated 20.04.2015. NCDRC find negligence of the O.P., which resulted into diminution of vision of left eye of the Complainant. The State Commission erred which did not properly consider the medical record, the literature on subject and the observation of Ethical Committee of MCI. NCDRC allowed the Revision Petition and the order of the State Commission was set aside. In NCDRC’s view, the award of the compensation by the District Forum, was just and proper, however the interest of 12% was considered on higher side. NCDRC concluded that therefore, in the ends of justice, the interest rate was modified to 6%. This paper helps ophthalmologists to understand legal requirement of deficiency in service, medical negligence and professional misconduct from ethical point of view, importance of medical literature, medical record and second opinion and expert opinion along with role of state medical council and National Medical Commission in regulating medical practice, thus, help in improving the quality of services in conducting cataract operations in future.
Keywords: Ethics committee; Cataract; Vision; Second opinion; Medical literature